Explaining Organizational Citizenship Behavior Among Chinese Nurses Combating COVID-19 - Zhang H; Zhao Y; Zou P; Lin S; Mu S; Deng Q; Du C; Zhou G; Wu J; Gan L (Dove Medical Press, 2021)
Hui Zhang,1,* Yi Zhao,2,* Ping Zou,3 Shuanghong Lin,2 Shaoyu Mu,4 Qiansu Deng,5 Chunxue Du,1 Guanglan Zhou,1 Jiang Wu,2 Lu Gan2 1Department of Cardiology, Guizhou Provincial People’s Hospital, Guiyang, 550002, Guizhou, People’s Republic of China; 2Department of Nursing, Hubei NO.3 People’s Hospital of Jianghan University, Wuhan, People’s Republic of China; 3Department of Scholar Practitioner Program, School of Nursing, Nipissing University, Toronto, M6J 3S3, Ontario, Canada; 4Department of Nursing, Nursing College of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 5Department of Nursing, Chongqing Traditional Chinese Medicine Hospital, Chongqing, 400011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuanghong LinDepartment of Nursing, Hubei NO.3 People’s Hospital of Jianghan University, Wuhan, People’s Republic of ChinaTel +8618771059373Email 18771059373@163.comBackground: Little is known about the associated factors with organizational citizenship behavior among Chinese nurses combating COVID-19. The aim of the present study was to investigate the relationships between autonomy, optimism, role conflict, work engagement, and organizational citizenship behavior based on moderated mediation models among Chinese nurses combating COVID-19.Methods: This cross-sectional study was performed on a sample of 368 nurses supporting the COVID-19 epidemic in Wuhan Leishenshan Hospital, China. According to the Job Demands-Resources model, two moderated mediation models were tested, in which autonomy/optimism was associated with organizational citizenship behavior through work engagement, when role conflict served as a moderator.Results: This current study found the mediating effect of work engagement and the moderating effect of role conflict on the relationship between autonomy/optimism and organizational citizenship behavior among nurses. Of note, nurses working in the COVID-19 epidemic viewed role conflict as challenge job demands rather than hindrance job demands.Conclusion: Based on the findings, organizational citizenship behavior can be affected by work engagement and role conflict. Nursing management is suggested to put emphasis on work engagement and role conflict among nurses supporting the COVID-19 epidemic.Keywords: the job demands-resources model, autonomy, optimism, organizational citizenship behavior, nurses, COVID-19